DEVELOPMENT AND VALIDATION OF A SIMPLE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY UV METHOD FOR THE DETERMINATION OF VINORELBINE - A CHEMOTHERAPEUTIC DRUG IN SPIKED HUMAN PLASMA - Mallu, Useni Reddy; Rao Anna, Venkateswara; Kasimala, Bikshal Babu (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Vinorelbine (VNRB) is a chemotherapeutic drug used to treat non-small cell lung cancer and breast cancer. Literature survey reveals that there are no reverse-phase high-performance liquid chromatography (RP-HPLC) methods reported for the estimation of VNRB in spiked human plasma. Hence, the present work aimed to develop a simple and efficient RP-HPLC method for the estimation of VNRB in human plasma. Methods: Specimen preparation for the measurement of VNRB was performed through liquid-liquid extraction using methanol as extracting solvent and reconstructed with mobile phase. Paclitaxel (PCTX) was used as internal standard. HPLC method was optimized and validated as per the US FDA bioanalytical guidelines. VNRB and internal standard were separated on Kromasil® C18 (250×4.6 mm; id 5 μ) using acetate buffer (pH=5.9) and methanol in the ratio of 85:15 (v/v) at 1 ml/min flow rate. Eluted compounds were recorded using UV detector at 235 nm. Results: The retention time of PCTX and internal standard was found to be 4.3 and 9.0 min, respectively. The analytical measuring ranges were found to be 5–750 ng/ml (r2>0.9998). The method was found to be simple, accurate, precise, and stable and there is no interference of plasma matric components. Conclusion: The described HPLC method allows for the measurement of total and free PCTX in both plasma and cord blood and can utilize for the estimation of drug in pharmacokinetic studies.